Klobuchar and nequick g ionospheric models comparison for multi-gnss single-frequency code point positioning in the Brazilian region - Setti Júnior, Paulo de Tarso [UNESP]; Alves, Daniele Barroca Marra [UNESP]; da Silva, Crislaine Menezes [UNESP] (FapUNIFESP (SciELO), 2019)
One of the main error sources in GNSS positioning comes from the ionosphere, an atmospheric layer that stays in the signal path between the satellite and the receiver. For single frequency positioning, the ionospheric effects can be minimized by using an ionospheric model e.g. Klobuchar or NeQuick G. These models are respectively associated to GPS and Galileo systems through their navigation messages, which broadcast coefficients that describe the worldwide ionospheric behavior, and the calculated ionospheric delay is then applied in the pseudorange observations. In this paper, it is presented a comparison between these two models in multi-GNSS (GPS and Galileo) single frequency point positioning, considering two Brazilian stations at different magnetic latitudes, and covered months of weak and strong ionospheric activity from 2013 to 2018. The results indicate a better performance of NeQuick G model compared to the Klobuchar. Considering all the analyzed periods and stations, Klobuchar improves the positioning accuracy in 16% and 50% in periods of weak and strong ionospheric activity, respectively, while NeQuick G improves the accuracy in 31% and 55%.
Keywords: Galileo; Klobuchar; NeQuick; Point Positioning